CROSS-BORDER PROPERTY OWNERSHIP DALAM PERSPEKTIF HUKUM INTERNASIONAL: SUATU STUDI PERBANDINGAN NEGARA - Akhmad Kautsar Fattah; Handar Subhandi Bakhtiar (Jurnal Humaniora & Sosial Sains, 2025)
This study addresses the issue of cross-border property ownership from the perspective of international law, with a focus on comparing Indonesia with several other countries. The main objective of this research is to examine how international law accommodates property ownership by foreign nationals and the mechanisms available for resolving disputes arising from it. The research employs a normative legal method using statutory, analytical, and comparative approaches. The findings indicate that regulations concerning property ownership by foreign nationals largely depend on the national sovereignty of each country. Indonesia, for example, through the principle of nationality under the Agrarian Law (UUPA), restricts property ownership exclusively to Indonesian citizens, with limited exceptions in the form of usage rights (hak pakai). However, in practice, legal loopholes exist through nominee schemes and foreign investment mechanisms such as the establishment of foreign-owned companies (PT PMA). Meanwhile, countries like Singapore and Japan adopt more open approaches toward foreign property ownership. In terms of dispute resolution, international law provides access to international arbitration forums such as ICSID, which serve as alternatives for foreign investors seeking fair and neutral legal protection. Therefore, while international law does not directly regulate the substance of property ownership, it plays a crucial role in shaping the framework for investment protection and cross-border property dispute resolution.